Exploring the Social Impacts of Events. - Richards, Greg (Routledge advances in event research series., 2013)
Social impacts are increasingly used as one of the main justifications for staging and funding events, and yet there is very little empirical evidence on the extent to which these impacts are realised by different kinds of events or in different settings. This timely volume fills this gap by being the first to explore the different social aspects of events, looking in particular at the role of events in developing social capital, social cohesion and participation in local communities. Based on cutting edge empirical research, it evaluatesthe contribution of both cultural and sports ev.